PENGARUH STABILITAS PEKERJAAN, PENGAYAAN PEKERJAAN DAN KEPUASAN KERJA TERHADAP KOMITMEN KARYAWAN - Ade Jaya Sutisna; Tati Rohaeti (Universitas La Tansa Mashiro, 2022)
The purpose of this thesis is to investigate the mediating effect of job satisfaction on the relationships between job stability and job enrichment on employee commitment of clinic in the health organization. Data were collected from 54 clinic employees working in Mutiara Medika Rangkasbitung Clinic of Lebak Regency. Partial Least Squares were used for analysis since it is considered the best method to analyze the data containing both reflective and formative indicators. Results suggest that job satisfaction fully mediates the effects of job stability and job enrichment on employee commitment and the positive effects of the job stability and job enrichment on job satisfaction. This thesis confirms that job stability and job enrichment on employee commitment affect employee commitment via job satisfaction. Hence, job stability and job enrichment embed clinic employees in their jobs, and they are likely to improve their commitment. Furthermore, low levels of job stability and job enrichment must be addressed with a good environment clime in order to increase job satisfaction..